Awareness and perception of vasectomy among antenatal women in a tertiary health facility in southeast Nigeria - Ikeako, Lawrence C.; Nnagbo, Johnpaul E.; Umeh, Uchenna A.; Ezegwui, Hyginus U.; Chigbu, Chibuike O.; Ajah, Leonard; Onwudiwe, E. N.; Okeke, Tochukwu C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Vasectomy is a safe alternative to bilateral tubal ligation (BTL) in achieving permanent sterilization but not popular in developing countries. As part of the efforts to increase popularity as well as acceptance of vasectomy in the developing countries, its awareness among women needs to be assessed. The study was undertaken to determine the awareness and perceptions of vasectomy among antenatal attendees in a tertiary health institution southeast Nigeria. Methods: This was a questionnaire-based cross-sectional study in which pregnant women visiting University of Nigeria Teaching Hospital, Enugu (UNTH) antenatal clinic from 1st June – 30th November 2017 were recruited. Data was collected using structured questionnaire. Two hundred (200) self-administered questionnaires were completely filled and analyzed by means of descriptive and inferential statistics including means frequencies and x^2-tests at the 95% confidence level (CL). Results: Of the 200 respondents, 146(73%) were completely unaware of the existence of vasectomy while 54(27%) were aware. Of those who were aware, 41(75.9%) accepted its use as a family planning method for men. The commonest reason for acceptance was the fear of infidelity among their husbands, 17(41.5%). The intention to use was however low as 24(44.4%) of those who accepted vasectomy disapproved of its use by their husbands and the main reason for disapproval was “weakens husband’s sexual performance,” (33.3%). Tertiary level of education of the respondents was 5.3 times independently associated with the acceptance of vasectomy. Conclusions: The awareness is low and there are several misperceptions about vasectomy among the women in Enugu. Tertiary education of the women however improves the choice of vasectomy as a permanent contraceptive option. There is the need for educational programmes in line with the numerous advantages of vasectomy so as to counteract the misperceptions especially those regarding sexual relationship.